Functionality of self-care for pregnancy mobile applications: A review study - Behnaz Pouriayevali; Asghar Ehteshami; Shahnaz Kohan; Sakineh Saghaeiannejad-Isfahani (Wolters Kluwer Medknow Publications, 2022)
Self-care may help prevent pregnancy complications and mortality by informing parents. Mobile health applications (apps) can help individuals to improve the quality of self-care. Although it has been claimed that mobile apps have various benefits, their functionalities in pregnancy self-care are still unclear. A clear understanding of current apps can help researchers, practitioners, and app developers to identify appropriate functionalities for new development and future refinement of current apps. This review endeavored to identify appropriate functions for pregnancy self-care mobile apps and user interface (UI) features. The scope of this review integrates self-care for pregnancy apps published in Google Play and Cafe Bazaar (an Iranian Android marketplace), popular Android app stores, from July to October 2019 by sing the systematic search technique. All 4196 downloaded apps were installed, and it was found that 76 of them met the inclusion criteria. This way, their features were extracted and categorized by the conventional content analysis. Three main themes and 69 subthemes in terms of apps functionalities and their UI features were extracted as follows: 1) Training materials (maternal and paternal) with 27 subthemes; 2) self-care functionalities (consultations, fetus tracking, clinical examination, supportive assistance, and reminders) with 26 subthemes; and UI features with 16 subtheme. The findings underlined the mHealth solutions for pregnancy self-care and the need for development of the apps regarding the extracted functionalities and UI features; however, controlled trials are needed. It is recommended that transparent reporting of mHealth interventions needs to be prioritized to enable effective interpretation of the extracted data.